Strengthening Ecosystems and Biodiversity Conservation in Response To Climate Change In Saudi Arabia - Toukabri , Maher; Chaabi , Antar (European Journal of Sustainable Development, 2025)
This study aims to assess the impact of climate change on Saudi Arabia